1999
DOI: 10.1063/1.873735
|View full text |Cite
|
Sign up to set email alerts
|

Flow driven resistive wall instability

Abstract: The stability of a perfectly conducting fluid layer flowing along a magnetic field, parallel to a finitely conducting thin wall is examined. Finite layer width and compressibility of the fluid are shown to significantly lower the flow velocity required for instability to set in. The effect of axial flow on the stability of a cylindrical pinch surrounded by a resistive wall is examined. Flow is shown to have a destabilizing effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
1
7
1
Order By: Relevance
“…The dispersion relation given in Eq. ͑23͒ is identical to the one obtained recently by Veeresha et al 15 although these authors wrote the equation in a different form. It is helpful to re-write Eq.…”
Section: Solutions Of the Dispersion Relationsupporting
confidence: 79%
See 1 more Smart Citation
“…The dispersion relation given in Eq. ͑23͒ is identical to the one obtained recently by Veeresha et al 15 although these authors wrote the equation in a different form. It is helpful to re-write Eq.…”
Section: Solutions Of the Dispersion Relationsupporting
confidence: 79%
“…For a uniform incompressible slab of fluid in the presence of a uniform flow velocity along a uniform magnetic field it was shown that the flow velocity resulted in a resistive wall instability if v 0 Ͼͱ2c A where v 0 is the flow speed and c A the Alfvén speed. An extension of this model to a compressible plasma 14,15 showed that, in addition to this instability, a second resistive wall instability occurred when v 0 Ͼc S where c S is the sound speed, and for low beta conditions, c S Ӷc A . However, these very simple models are not relevant to a tokamak.…”
Section: Introductionmentioning
confidence: 97%
“…Such effects have been well studied in the literature, such as plasma flow in the presence of a resistive-wall [7]. In the present case, although the driving mechanism for the instability is different from the resistive-wall instability [8], it is clear that the instability will occur only due to the interaction of the wave with the electron E × B flow in the presence of electron collisions.…”
Section: Introductionmentioning
confidence: 66%
“…Such effects have been well studied in the literature, such as plasma flow in the presence of a resistive-wall [7]. In the present case, although the driving mechanism for the instability is different from the resistive-wall instability [8], it is clear that the instability will occur only due to the interaction of the wave with the electron E × B flow in the presence of electron collisions. This paper is organized as follows: In Sec.…”
Section: Introductionmentioning
confidence: 67%